TANGGUNG JAWAB PERUSAHAN DAMRI TERHADAP HILANGNYA BARANG PENUMPANG DI CABANG SINTANG - Stefanus Ngebi (Universitas Kapuas Sintang, 2022)
Transporting services is a vital means or activity in people’s lives. It shows a variety of factors. Transportation services often require treaties, such as transportation agreements. Agreements are used asa basis for the morning laws of those who have committed themselves to the alliance. Losing a passenger item was not immediately a passenger responsibility. In the transport of tickets that became the basis for the implementation of the agreement. Of course there are rights and obligations to be noticed and properly fulfilled. In this study, researchers used normative-empirical law research methods. This was necessary if the scientific writing did not deviate from the matter at hand. The research methodology is the study of frameworks carrying out research. The company is expected to be able to minimize damage or accidents to the delivery by inspecting the delivery beforehand in order to make sure that the delivery is safe and comfortable.